Probable Anti-Glutamate Decarboxylase 65 (Gad65) Antibody-Associated Cerebellar Ataxia. Clinical Case Report and Literature Review - Valinčiūtė, J.; Petkevičiūtė, P.; Balnytė, R.; Čiauškaitė, J. (Neurologijos seminarai, 2023)
Introduction. As more information about cerebellar ataxia induced by anti- GAD65 antibodies is accumulated, cerebellar dysfunction is increasingly associated with autoimmune causes. The prevalence of other neurological syndromes associated with anti- GAD65 antibodies has been estimated, but the occurrence of cerebellar ataxia of the same cause has not yet been reported. The clinical presentation and management of anti-GAD65 antibodies induced cerebellar ataxia are currently known only from single cases and small series reports.Case report. We present a clinical case of a 52-year-old woman who was admitted to the hospital due to dizziness, impaired coordination, occasional choking, and slurred speech. Diagnostic procedures were performed, in which anti-GAD65 antibodies and atrophic changes in the upper parts of the cerebellum were detected on brain MRI, which led to a possible diagnosis of anti-GAD65 antibody-associated cerebellar ataxia.Discussion and literature review. Patients tend to be women in their 60s with clinical symptoms such as gait and posture ataxia. Most patients present with nystagmus, dysarthria, and limb ataxia. To make the diagnosis, it is crucial to detect high titers of anti-GAD65 antibodies, do intrathecal anti-GAD65 antibody synthesis, and perform a brain MRI, which may reveal atrophy of the cerebellum as the disease progresses. Corticosteroids are one of the recommended treatment methods, which were effective in our case. Maintenance therapy is essential to prevent relapse of the disease.
Keywords: anti-GAD65 antibody; cerebellar ataxia